The Northern Sea Route : history, challenges and prospects - Ulaeva, Liliia, 1983- (2020)
The Northern Sea Route has long been the transit artery for the Russian North. In addition to bringing goods to meet the needs of its residents, the NSR is essential for bringing Russia's extracted natural resources out. These aspects determine its significance for supporting development of the Russian economy. Ongoing climate changes, as well as the growth of human activities, including fishing, extractive industries, interest in transit shipping and the increase of shipping in general create increasing pressure and additional stresses on the sensitive marine environment in the area and the peoples who live nearby. This thesis examines the history, development and prospect for the Northern Sea Route in light of Russia’s legal, socio-economic, political and security interests and policies. The natural resources of the Arctic are of strategic importance for Russia's economy and national security. Activities in the extractive industry are increasing and their importance for the Russian economy is inextricably linked with the need for the growth of shipping for resource extraction. But what exactly is the role of the NSR in Russia's economic development and how important is the NSR for Russia other than as a transport highway for cargo delivery? An analysis of the legal, socio-economic and political components of the Russian governance of the marine Arctic will allow us to conclude that the significance of the NSR for Russia is highly important. Moreover, the analysis of Russia's strategic documents will allow us to understand the scale of planned projects in the Arctic. However, does Russia currently have the capacities for safe implementation of all the existing values of the NSR? And what are the current challenges for the Russian Maritime Arctic in the light of navigation and the NSR that should be taken into account? After analyzing all these topics in this study, the conclusion will be made that the importance of the NSR also carries fundamental challenges with it that require solutions or at least a ...